Frequency dependence of level depletion in Na clusters and in C 2H4 - Vidal, S.; Wang, Z. P.; Dinh, P. M.; Reinhard, Paul-Gerhard; Suraud, E. (Journal of Physics B-Atomic Molecular and Optical Physics, 2010)
In the framework of time-dependent density-functional theory, we study electron emission from Na clusters and the C2H4 molecule as induced by irradiation with an intense pulse. The collision of a charged projectile with C2H4 is also explored for comparison. We look in particular at the level depletion, i.e. the electron loss in each single-electron level separately. It is found that the distribution of electron loss depends sensitively on the photon frequency. Frequencies close to visible light remove electrons exclusively from the vicinity of the Fermi surface while light in the higher UV range (up to 20 eV for Na clusters and up to 136 eV for C2H4) depletes all levels, about equally strong, down to the deepest bound valence state. © 2010 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24